Change in cardiac geometry and function in CKD children during strict BP control: a randomized study - Matteucci, Maria Chiara; Wühl, Elke; Schaefer, Franz (Clinical journal of the American Society of Nephrology, 2013)
Background and objectives Left ventricular hypertrophy (LVH) and abnormal systolic function are present in a high proportion of children with CKD. This study evaluated changes in left ventricular (LV) geometry and systolic function in children with mild to moderate CKD as an ancillary project of the Effect of Strict Blood Pressure Control and ACE Inhibition on Progression of Chronic Renal Failure in Pediatric Patients trial. Design, setting, participants, & measurements Echocardiograms and ambulatory BP monitoring were performed at baseline and at 1- or 2-year follow-up in 84 patients with CKD and 24-hour mean BP above the 50th percentile and/or receiving fixed high-dose angiotensin converting enzyme inhibition and randomized to conventional or intensified BP control. Results LVH prevalence decreased from 38% to 25% (P<0.05). Changes in LV mass index (LVMI) were restricted to patients with LVH at baseline (−7.9 g/m2.7; P<0.02). Changes in LVMI were independent of randomization, reduction in BP, hemoglobin, and estimated GFR. A significant increase in midwall fractional shortening was observed in the total cohort (P<0.05), and was greater in the intensified group compared with the conventional BP control group (12%±1.9% versus 8%±1.5%; P=0.05). In multivariate analysis, improvement in myocardial function was associated with reduction in BP (r=−0.4; P<0.05), independently of LVMI reduction. Conclusions In children with CKD, angiotensin converting enzyme inhibition with improved BP control, LVH regression, and improved systolic function was observed within 12 months. Lowering BP to the low-normal range led to a slightly more marked improvement in myocardial function but not in LVMI.
Published online February 7, 2013
Gesehen am 20.06.2018